Rare Continuity Revisited via δb-open Sets - ŞENGÜL, UĞUR (My University, 2024)
In this paper we introduce and study the concept of rare δb-continuity in topological spaces as a generalization of rare continuity and weak δb-continuity. We investigate several properties of rarely δb-continuous functions. Rare δb-continuity implied by rare δ-continuity and implies rare b-continuity. We also introduce the concept of I.δb-continuity, which is weaker than δb-continuity and stronger than rare δb-continuity.
Keywords: Matematik; Temel Bilimler; Mathematics; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; MATEMATİK; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MATHEMATICS; MULTIDISCIPLINARY SCIENCES; Mantık; Geometri ve Topoloji; Ayrık Matematik ve Kombinatorik; Multidisipliner; Fizik Bilimleri; Logic; Geometry and Topology; Discrete Mathematics and Combinatorics; Multidisciplinary; Physical Sciences; δb-open sets; rare δb-continuity; I.δb-continuity